Introduction to the Case Studies - Kirsten Roberts Lyer; Ilyas Saliba; Janika Spannagel (University Autonomy Decline: Causes, Responses, and Implications for Academic Freedom, 2023)
This chapter introduces the five qualitative case studies written by country experts on Bangladesh, India, Mozambique, Poland, and Turkey, which serve to deepen an understanding of current trajectories regarding academic freedom and university autonomy through in-depth description and analysis. The studies are based on standardized academic freedom case study guidelines that are designed to facilitate systematic comparisons. This chapter explains the research approach, as well as the case selection rationale, which makes use of the Academic Freedom Index data to identify countries with severe declines in university autonomy. Finally, this introductory chapter briefly introduces the five country studies and their authors.
Additional information: The publication of the open access book "University Autonomy Decline: Causes, Responses, and Implications for Academic Freedom" was funded by the Open Societies Foundation and the Open Access Publishing Fund of the Leibniz Association.
Keywords: 330